DEVELOPMENT OF OUTBOUND MINI GAME MODEL BASED ON NATURAL POTENTIAL TO DEVELOP ROUGH MOTOR SKILLS OF CHILDREN AGED 5-6 YEARS - Irfah Aulaini Damanik; Aman Simare-mare; Abdul Murad (Sensei International Journal of Education and Linguistic, 2021)
This research is a type of research development (Research and Development) that aims to know the feasibility of outbound mini-game models based on natural potential and know the effectiveness of outbound mini-game models based on natural potential. This development uses addie model which includes 5 steps, namely: Analize, Design, Development, Implemention, and Evaluation. The subjects of this study were children of group B age 5-6 years RA Nurul Huda Denai Sarang Burung as many as 10 children field trials and as many as 5 children trial small groups. Data collection instruments in the form of validation assessment sheets of design experts, rough motorists, early childhood experts, and teacher response questionnaires in assessing products. The study produced products that met the validation of design experts, rugged motorists, and early childhood experts, with an average percentage rate of 93.0%, which said the category was very valid and worth using. teacher response reached 92.3% with excellent criteria. The results of this study are outbound mini-game models packaged in compact disk.. The game model developed is effective in improving the child's rough motor skills. this can be seen from wilcoxon sign-rank difference test with 0.004 result. Signification result 0.004<0.05 which means there is a significant change between the ability of the child before and after treatment.